MODEL OPERASIONAL PERBANKAN SYARIAH - Zulkifli Zulkifli (AL-IQTISHAD, 2021)
The purpose of this research are 1). To know the Islamic Banking Operational Model based on the intermediation pattern 2). To find out the Islamic Banking Operational Model based on the pattern of fund pools 3). To find out the Islamic Banking Operational Model based on the financing segmentation pattern. The methodology used in this research is a literature review, with various references related to the theme of the problem.The results showed 1). Financial intermediation function. Islamic banking intermediation, namely financial intermediation and social intermediation. 2). The collection of funds in Islamic banks can be in the form of demand deposits, savings and time deposits. 3). In the business of financing principles, there are three schemes in conducting contracts at Islamic banks, namely: Profit Sharing Principles, Sale and Purchase Principles and Lease Principles.